Characteristics of Si-photonics devices - Koh, Janelle Shu En (Nanyang Technological University, 2023)
Polarization Extinction Ratio (PER) is an important parameter in optical systems, determining signal quality, data accuracy, and overall device performance. This study investigates the use of a Fiber Bench, Linear Polarizer, and Half-Wave Plate to improve PER measurements and optimize polarization control within the system. The Fiber Bench provides a sturdy platform for perfect component alignment, resulting in minimal angular motion and maximum coupling efficiency. The Linear Polarizer is an important component in filtering incident light, enabling only the required polarization state to pass through. The addition of a Half-Wave Plate gives additional polarization control, allowing changes to fine-tune the system for best PER. The experimental procedure entails properly aligning the components on the Fiber Bench, systematically altering the polarization states with the Linear Polarizer and Half-Wave Plate, and measuring the resulting PER. The collected data is examined to determine which configurations produce the highest PER, resulting in increased signal quality and less cross-polarization effects. The study's goal is to show the importance of accurate alignment and controlled polarization in generating high PER values. The discoveries have ramifications for a wide range of applications, including fiber-optic transmission, sensors, and interferometric devices. This study gives insights into enhancing polarization control techniques for improved PER performance by exploiting the capabilities of the Fiber Bench, Linear Polarizer, and Half-Wave Plate.